Uganda: elephants, people and fire in Gulu District - Ian Parker (Pachyderm)
In this historical essay Uganda’s Gulu District is as it was in colonial times. Today this area contains the districts of Moyo, Adjumani, Amuru and Gulu. It focusses on gross environmental change mediated by elephants, people and fire within it from before the colonial era to the present, complementing my previous paper on the same topics in Bunyoro. Most of the District was peopled by the Acholi (Acoli), though in its north the Madi straddled the Nile between Gulu east of the river and West Nile District to the west. In slightly more than a century, elephants changed areas of woodland and forest to open, treeless grassland from which they were then replaced by people and largely treeless farmland. However, while basic patterns have similarities to those in Bunyoro they were less well defined as the District was not studied as closely.